Pengaruh Pelatihan Kerja, Pengalaman dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada Klinik Kecantikan Pipit Beauty Care Pamekasan) - Karomi Ash shiddiqi; Muhammad Mansur; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This research is a descriptive quantitative study which to examine and analyze the effect of work training, experience and work environment on employee performance in pamekasan beauty care pipelines, The population in this study were all employees of pamekasan pipit beauty care and the sample of this study used a saturated sample technique with a total of 35 employees. The data analysis method used in this research is descriptive analysis, instrument test, normality test, classical assumption test, multiple linear regression analysis and hypothesis testing. The results of this study found a conclusion, namely that partially job training has no effect on employee performance, experience has a positive effect on employee performance, work environment has a positive effect on employee performance, while simultaneously job training, experience and work environment have a positive effect on employee performance. Keywords : Job training, Experience, Work Environment, Employee Performance